Calcitonin gene-related peptide attenuated discogenic low back pain in rats possibly via inhibiting microglia activation - Weixin Xie; Fan Li; Yi Han; Xiaoying Chi; Yi Qin; Fan Ye; Zhanchun Li; Jie Xiao (Heliyon, 2024)
Discogenic low back pain (DLBP) is a multifactorial disease and associated with intervertebral disc degeneration. Calcitonin gene-related protein (CGRP) plays a critical role in pain processing, while the role in DLBP remains unclear. This study aims to investigate the anti-nociceptive role and related mechanisms of CGRP in DLBP. Here we established the DLBP rat and validated the model using histology and radiography. Minocycline, a microglial inhibitor, and CGRP were intrathecally injected and the behavioral test was performed to determine hyperalgesia. Further, BV2 microglial cells and microglial activation agent lipopolysaccharide (LPS) were employed for the in vitro experiment. We observed obvious lumbar intervertebral disc degeneration and hyperalgesia at 12 weeks postoperation in DLBP group, with significantly activated microglia in the spinal cord. CGRP treatment significantly inhibited the upregulation of proinflammatory cytokines and NLRP3/caspase-1 expression induced by LPS in BV2 cells, whereas treatment with CGRP alone had little effect on BV2 cells. The intrathecal injection of CGRP into DLBP rats relieved mechanical and thermal hyperalgesia, reverted the microglial activation and decreased the expression of NLRP3/caspase-1, similar to the effects produced by minocycline. Our results provide evidence that microglial activation in the spinal cord play a key role in hyperalgesia in DLBP rats. CGRP alleviates DLBP induced hyperalgesia and inhibits microglial activation in the spinal cord. Regulation of CGRP and microglial activation may provide a new strategy for ameliorating DLBP.